2016
DOI: 10.1161/jaha.116.003738
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Smoking Cessation, and Measures of Subclinical Atherosclerosis in Multiple Vascular Beds in Japanese Men

Abstract: BackgroundSmoking is an overwhelming, but preventable, risk factor for cardiovascular diseases (CVD), although smoking prevalence remains high in developed and developing countries in East Asia.Methods and ResultsIn a population‐based sample of 1019 Japanese men aged 40 to 79 years, without CVD, we examined cross‐sectional associations of smoking status, cumulative pack‐years, daily consumption, and time since cessation, with subclinical atherosclerosis at 4 anatomically distinct vascular beds, including coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
2
29
1
Order By: Relevance
“…Limited studies have been conducted to assess associations of smoking or smoking cessation on markers of inflammation such as hsCRP,5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 and even fewer studies have assessed measures of subclinical atherosclerosis 16, 17, 18, 19, 20, 21. These studies have generally shown higher levels of hsCRP among current and former smokers compared with nonsmokers5, 6, 9, 10, 12, 13, 14, 15 and decreased levels after smoking cessation, albeit slower than systolic blood pressure and total cholesterol and LDL‐C 8, 11, 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies have been conducted to assess associations of smoking or smoking cessation on markers of inflammation such as hsCRP,5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 and even fewer studies have assessed measures of subclinical atherosclerosis 16, 17, 18, 19, 20, 21. These studies have generally shown higher levels of hsCRP among current and former smokers compared with nonsmokers5, 6, 9, 10, 12, 13, 14, 15 and decreased levels after smoking cessation, albeit slower than systolic blood pressure and total cholesterol and LDL‐C 8, 11, 12.…”
Section: Discussionmentioning
confidence: 99%
“…4 Deaths due to smoking-related cardiovascular disease (CVD) are generally preceded by subclinical cardiovascular injury that may be detected early in the disease process. Interest is rising in finding biomarkers of CVD-related injury in asymptomatic persons, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and there is a need to identify sensitive biomarkers of smoking-related early subclinical cardiovascular damage. Such biomarkers may assist in risk identification and stratification among smokers.…”
mentioning
confidence: 99%
“…Also, there are already some studies about the risk factors of CPs or CIMT, for example, a study found that elevated resting heart rate is associated with an increased odds of CIMT and the presence of CPs (Wang, Zhang, Sun, Wang, & Cao, 2016). Another study revealed that when compared with nonsmoker, both former and current smokers have a greater risk of CIMT and CPs (Hisamatsu et al., 2016). There are also associations between dyslipidemia and CP; a cross‐sectional study revealed that TG is an independent predictor of CP risk (Mi et al., 2016), and another study showed that combined LDL‐C and HDL‐C levels can predict the presence of CPs, and the LDL‐C/HDL‐C ratio can act as an independent index for CIMT (Yang et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking behavior may wield a strong influence on an association between coffee consumption and CVD risk. Smokers are often more frequent coffee drinkers, and they are also inherently at greater risk of coronary artery disease and positively associated with subclinical atherosclerosis . Smoking may also intercede in the pathways through which coffee constituents are hypothesized to mediate effects on this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers are often more frequent coffee drinkers, 39 and they are also inherently at greater risk of coronary artery disease 39 and positively associated with subclinical atherosclerosis. 40,41 Smoking may also intercede in the pathways through which coffee constituents are hypothesized to mediate effects on this disease. If caffeine and coffee-derived antioxidants are important mediators of the association between coffee consumption and subclinical atherosclerosis, it is possible that deleterious effects of smoking overwhelm the influence of coffee intake on early CVD injury.…”
Section: Discussionmentioning
confidence: 99%